Study of hypoxia driven pancreatic cancer development - Gupta, Nikhil (Nanyang Technological University, 2020)
Pancreatic cancer is one of the leading causes of death worldwide among all cancer types due to difficulty detecting in early-stages of disease. Poor understanding of the mediators that drive the progression of solid hypoxic tumors remains one of the significant challenges in treating pancreatic cancer. Hypoxia often correlates with poor survival of patients with pancreatic cancer. Pancreatic cancer cell adaptation to limited oxygen delivery promotes the induction of treatment-resistant and aggressive phenotype by triggering tumor evolution and metastasis at an early stage of tumor development. The hypoxic environment in tumor resists the infiltration of T-cells as compared to the normoxic area of the same tumor, suggesting its role in immunosuppression. Furthermore, hypoxia-induced exosomes also promote cancer development by enhancing migration, angiogenesis, and early metastasis in solid tumors. However, the precise mechanism of exosome-mediated tumor progression remains unclear. We, therefore, used a heavy isotope ‘pulse/trace’ proteomic approach to determine how hypoxia alters pancreatic tumor expression of proteins that confer treatment resistance, promote metastasis, and suppress host immunity. Using this method, we identified that hypoxia stress stimulates pancreatic cancer cells to rapidly translate proteins that enhance metastasis (NOTCH2, NCS1, CD151, NUSAP1), treatment-resistance (ABCB6), immune suppression (NFIL3, WDR4), angiogenesis (ANGPT4, ERO1α, FOS), alter cell metabolic activity (HK2, ENO2), and mediate growth-promoting cytokine responses (CLK3, ANGPTL4). Proteome profiling of exosomes identified elevated expression of proteins that involved in metabolism, cytoskeleton assembly, signal transduction, and immune suppression. Hypoxia also regulates the expression of major immune checkpoint proteins (CTLA-4, TIM-3, GAL-9) in MIAPaCa-2 cells and exosomes, suggesting its role in immunosuppression. Database mining confirmed that the elevated gene expression of these hypoxia-induced mediators is significantly associated with poor patient survival in various stages of pancreatic cancer. Among these proteins, the oxidoreductase enzyme ERO1α was highly sensitive to induction by hypoxia stress across a range of different pancreatic cancer cell lines and was associated with particularly poor prognosis in human patients. Consistent with these data, genetic deletion of ERO1α substantially reduced growth rates and colony formation in pancreatic cancer cells when assessed in a series of functional assays in vitro. Accordingly, when transferred into a mouse xenograft model, ERO1α-deficient tumor cells exhibited severe growth restriction and negligible disease progression in vivo. Tandem Mass Tags (TMT) proteomics and co-immunoprecipitation (Co-IP) approaches were used to identify the proteins regulated by ERO1α and its interacting partners. TMT proteomic analysis showed a significant fraction of high confident proteins involved in VEGF signaling, protein folding, and metabolic process were severely suppressed in ERO1α KO cell lines. Collectively, these data indicate that ERO1α is a potential prognostic biomarker and novel drug target for pancreatic cancer therapy.